Nanofiber Alignment Regulates NIH3T3 Cell Orientation and Cytoskeletal Gene Expression on Electrospun PCL+Gelatin Nanofibers. - Timothy Fee; Swetha Surianarayanan; Crawford Downs; Yong Zhou; Joel Berry (PLoS ONE)
To examine the influence of substrate topology on the behavior of fibroblasts, tissue engineering scaffolds were electrospun from polycaprolactone (PCL) and a blend of PCL and gelatin (PCL+Gel) to produce matrices with both random and aligned nanofibrous orientations. The addition of gelatin to the scaffold was shown to increase the hydrophilicity of the PCL matrix and to increase the proliferation of NIH3T3 cells compared to scaffolds of PCL alone. The orientation of nanofibers within the matrix did not have an effect on the proliferation of adherent cells, but cells on aligned substrates were shown to elongate and align parallel to the direction of substrate fiber alignment. A microarray of cyotoskeleton regulators was probed to examine differences in gene expression between cells grown on an aligned and randomly oriented substrates. It was found that transcriptional expression of eight genes was statistically different between the two conditions, with all of them being upregulated in the aligned condition. The proteins encoded by these genes are linked to production and polymerization of actin microfilaments, as well as focal adhesion assembly. Taken together, the data indicates NIH3T3 fibroblasts on aligned substrates align themselves parallel with their substrate and increase production of actin and focal adhesion related genes.